Hubungan Tingkat Pengetahuan Dengan Sikap Lansia Dalam Pencegahan Osteoporosis di Desa Ketanjung Karanganyar Demak - Mukhlishoh Mukhlishoh; Akhmad Safi'i; Athi’ Linda Yani; Devin Prihar Ninuk (Tirtayasa Medical Journal, 2026)
Osteoporosis is a common condition among the elderly that can be reduced through improved knowledge and a positive attitude toward prevention. This study used a quantitative cross-sectional design to examine the relationship between knowledge level and attitude toward osteoporosis prevention among elderly residents of Ketanjung Village, Karanganyar, Demak. A total of 64 participants meeting the inclusion criteria—female elderly, willing to participate, not in an emergency condition, registered at the community health center as osteoporosis patients, able to carry out activities independently, and fully conscious—were selected using purposive sampling. Exclusion criteria included absence during the activity or not being registered at the health center. Data were collected using a validated and reliable closed-ended questionnaire, and analyzed with the Chi-Square test. Results showed that 70% of respondents had good knowledge of osteoporosis prevention, and 61% had a positive attitude toward preventive measures. Statistical analysis revealed a significant relationship between knowledge and attitude (p = 0.02), indicating that higher knowledge levels are associated with more positive attitudes. These findings suggest that structured, ongoing health education can enhance awareness and promote positive behavior toward bone health in the elderly. The study’s limitations include its restriction to one village and a small sample size, so further research with larger, more diverse populations is recommended to improve generalizability.